FEASIBILITY OF THE FUNGI MATERIAL TEACHING MODULE AS A LEARNING RESOURCE FOR HIGH SCHOOL STUDENTS - Falah, Fajrul; Qurrotul Uyuni; Roudhoutul Aulia Rochim (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
This study investigates the utilization of Teaching Modules as a pedagogical tool in biology education, with a specific focus on the subject of Fungi. Recognized for their practicality and portability, Teaching Modules are deemed as efficacious educational aids to facilitate learning endeavors, both within classroom settings and in practical field applications. The research centers on the development and validation of Teaching Modules tailored for the Fungi curriculum, targeting students in the tenth grade of high school. Employing the Research and Development (R&D) methodology, this inquiry rigorously evaluates Teaching Modules across content, language, and presentation dimensions. Expert evaluations, featuring input from subject matter specialists and media professionals, underscore the Teaching Modules' commendable quality, achieving a validation score of 90%. Conclusively, this investigation affirms the Teaching Modules' substantive merit and validity as educational media, particularly in assisting students in discerning diverse forms of Basidiomycota Fungi.